Manager’s gender and innovation: Empirical case in Pymes of Cali - Salas-Arbeláez, Laura; García-Solarte, Mónica; Azuero-Rodríguez, Andrés Ramiro (Universidad Pedagógica y Tecnológica de Colombia, 2018)
In recent years, innovation has become a vital and strategic activity for the performance of organizations. Face to this, the Small and Medium Enterprises (Pymes) have been forced to immerse themselves in innovative initiatives that allow them to encourage their business growth to remain in time. Few studies link organizations forms of innovation with manager’s gender, and those studies that exist, show that men do more innovation activities in companies than women. Following the precedent, this research aims to identify the effect of manager’s gender in the innovations in Pymes of the manufacturing and high technology  sector of Cali. Results show that there is no difference between men and women when doing innovation in organizations.